Programa Dinheiro Direto na Escola – PDDE: uma análise acerca das implicações na gestão escolar do ensino público no município de Imperatriz/MA - DANTAS, Clara Weinna Moura (2022)
The present work aims to analyze the Dinheiro Direto na Escola Program and its repercussions for public education in the city of Imperatriz/MA. Specifically, it seeks to understand the implications of the PDDE in Democratic Management. For studies carried out on the program in question, as well as studies of democratic management from which the data were carried out, were in order to assess information regarding the PDs of the PD. This research makes use of the epistemological method of dialectical materialism, characterizing itself as qualitatively, since this was a form of data analysis. Others, the use of bibliographic, documentary and field research presented in this construction, being the instruments and techniques that were used, respectively, both the semi-structured interview and a document analysis. An analysis of the data with a content analysis technique. The locus of research was a school in the municipal public network and it was in one of the neighborhoods of the city carried out in Imperatriz/MA, in which it was possible to analyze how the PDDE develops from the perspective of democratic management. Among the results of the collection and data, there was a policy that still cannot be ascertained from the results that the school deepens participatory management, in fact, it is an analysis of the auxiliary school in a participatory way. Scholarly, in view of the various school issues, as examples of its implementation, the community's lack of time to actively participate in issues related to the program.